EXOPOLYSACCHARIDE PRODUCTION AND ITS BIOACTIVITIES OF THE EDIBLE PLEUROTUS OSTREATUS IN SUBMERGED CULTURE - IWAN SASKIAWAN (SEAMEO BIOTROP, 2009)
Submerged cultures were used to study the influence of various carbon sources on the mycelial biomass and exopolysaccharide production of Pleurotus ostreatus. The antimicrobial and antioxidant activity of the exopolysaccharide were also determined. The yield of mycelial biomass of 7.06 g/l, 5.12 g/l, 4.66 g/l, and 2.96 g/l was obtained by utilization of maltose, glucose, lactose and starch as a carbon source, respectively. Furthermore, in the medium containing maltose, lactose, glucose, and starch produce 100.05 mg/l, 97.73 mg/l, 78.63 mg/l, and 70.45 mg/l of exopolysaccharide, respectively. The assay of antimicrobial and antioxidant activity showed that the exopolysaccharide is more active to inhibit the growth of B. subtilis rather than those of E. coli and S. cerevisiae. Furthermore, the exopolysaccharide was also indicated to have antioxidant activity.Key words: Pleurotus ostreatus, exopolysaccharide, antimicrobial activity, antioxidant activity